2021
DOI: 10.1136/bmjpo-2020-000987
|View full text |Cite
|
Sign up to set email alerts
|

Reducing COVID-19 risk in schools: a qualitative examination of secondary school staff and family views and concerns in the South West of England

Abstract: ObjectiveTo investigate student, parent/carer and secondary school staff attitudes towards school COVID-19 mitigation measures.MethodsRecruitment used school communication, community organisations and snowball sampling in South West England. Audio recorded online or phone individual/group semi-structured interviews were conducted in July–Septtember 2020 and lasted 30–60 min. Interviews focused on views towards social distancing, hand hygiene and testing. Framework analysis was performed on interview notes/tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 23 publications
2
35
1
Order By: Relevance
“…[18] The high acceptance of screening expressed by our participants mirrors qualitative evidence regarding the acceptance of broader COVID-19 prevention measures in schools in the UK. [7] We expand on this evidence by highlighting the acceptability and feasibility of home-based nasal sampling among primary school pupils.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…[18] The high acceptance of screening expressed by our participants mirrors qualitative evidence regarding the acceptance of broader COVID-19 prevention measures in schools in the UK. [7] We expand on this evidence by highlighting the acceptability and feasibility of home-based nasal sampling among primary school pupils.…”
Section: Discussionmentioning
confidence: 91%
“…However, the idea of large-scale screening efforts at schools was criticized both from an epidemiological perspective (regarding imperfect test performance, especially of RDTs), but also as being an unnecessary burden for school children. [4][5][6] While a study from Great Britain suggests that SARS-CoV-2 protective measures in schools are highly accepted among students and parents, [7] to the best of our knowledge there is no evidence available on the perceptions of and experiences with the implementation of testing for entrance screening in school settings and the effects on compliance with other safety measures (e.g., masks).…”
Section: Introductionmentioning
confidence: 99%
“…From crisis to opportunity: parents and schools can come together to prioritise student health and well-being Christopher Bonell , 1 Neisha Sundaram, 1 Russell M Viner 2…”
Section: Viewpointmentioning
confidence: 99%
“…In countries such as the UK where school closures have not been so extended, parents supported school closures but reported that loss of education for their children was a major concern. 1 Parents strongly supported the return to school in spring 2021 citing concerns about their children's loss of learning and well-being while not in school. 2 In US research, parents commented on their concerns for students' social and emotional development while not in school.…”
Section: Parents Value and Trust Schoolsmentioning
confidence: 99%
“…Previous research suggests that staff, students and parents are concerned about perceived risks of missed learning [8], and that these concerns may outweigh concerns about transmission of the virus.…”
Section: Summary Of Findingsmentioning
confidence: 99%